O Uso do Lúdico e jogos como recurso didáticos no ensino de adição para alunos com Síndrome de Down - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Teaching resources are of great importance in the education of students with Special Educational Needs. The bearer of Down Syndrome has a delay in global development, speech difficulties and a deficit in memory, as they do not accumulate information in the long term. These characteristics make it difficult to learn and understand about the school life of these students. The problem that will guide this research will be in the following question: How can children's literature, games and educational software contribute to the learning of students with Down Syndrome? Our objective, therefore, is to investigate whether and/or how children's literature associated with games can contribute to the learning of adding integers (0 to 9) by students with Down Syndrome. The research was developed using observation and case study. Pedagogical materials were built, seeking to captivate students' attention by inserting their social and cultural context in the activities. The results indicated the importance of individual assistance to students with disabilities, and the need to diversify methodologies.
Keywords: Síndrome de Down; Inclusão; Adição; Jogos; Literatura; Down Syndrome; Inclusion; Addiction; Games; Literature; CIENCIAS HUMANAS::EDUCACAO